2007
DOI: 10.1007/s10637-007-9043-x
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel–ifosfamide combination in patients with HER2-non-overexpressing advanced breast cancer failing prior anthracyclines

Abstract: The feasibility of the docetaxel-ifosfamide combination, as well as the definition of maximum tolerated doses (MTD) in a previous phase I study, led us to continue evaluating the regimen in an extended phase II study in patients with HER2-non-overexpressing, anthracycline pre-treated advanced breast cancer. Patients with histologically confirmed metastatic breast cancer failing prior anthracycline-based chemotherapy were treated with docetaxel 100 mg/m2 over 1 h on day 1 followed by ifosfamide 5 g/m2 divided o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…phase I/II studies that have combined ifosfamide with other agents for treating advanced breast cancer patients, such as doxorubicin, (13) paclitaxel (14) and docetaxel (15,16) and these studies have demonstrated the feasibility of considerably high ifosfamide doses as well as the substantial activity of the employed combinations.…”
Section: Purposementioning
confidence: 99%
“…phase I/II studies that have combined ifosfamide with other agents for treating advanced breast cancer patients, such as doxorubicin, (13) paclitaxel (14) and docetaxel (15,16) and these studies have demonstrated the feasibility of considerably high ifosfamide doses as well as the substantial activity of the employed combinations.…”
Section: Purposementioning
confidence: 99%